2019
DOI: 10.1007/s00248-019-01405-8
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Tolerant Fungal Communities Are Delineated by High Zinc, Lead, and Copper Concentrations in Metalliferous Gobi Desert Soils

Abstract: The soil fungal ecology of the southern Gobi region of Mongolia has been little studied. We utilized the ITS1 region from soil DNA to study possible influences on soil fungal community variation. In the sample network, a distinctive fungal community was closely associated with high zinc (Zn), lead (Pb) and copper (Cu) concentrations. The pattern of occurrence suggests that high metal concentrations are natural and not a product of mining activities. The metal-associated fungal community differs little from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…Beneficial mutations resulted from recombination events, upon repair of double strand breaks induced by HMs, or horizontal gene transfer events [92][93][94] can grant isolate-unique HM resistance. The diversity and abundance of fungi isolated herein are in accordance with previous data describing Ascomycota as dominant in both natural and HM-contaminated soils [36,38,69,[95][96][97], and Mucoromycota as less frequently recovered from soil with multi-toxic elemental contaminations [69].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Beneficial mutations resulted from recombination events, upon repair of double strand breaks induced by HMs, or horizontal gene transfer events [92][93][94] can grant isolate-unique HM resistance. The diversity and abundance of fungi isolated herein are in accordance with previous data describing Ascomycota as dominant in both natural and HM-contaminated soils [36,38,69,[95][96][97], and Mucoromycota as less frequently recovered from soil with multi-toxic elemental contaminations [69].…”
Section: Discussionsupporting
confidence: 90%
“…The cosmopolitan nature and versatility of these two ascomycetous genera explain their high incidence at the investigated site [ 100 , 101 ]. The preponderance of Fusarium and of other genera identified here (i.e., Penicillium , Lecanicillium, and Phoma ) has also been reported in contaminated areas or substrates containing Cu, Pb, or Zn [ 71 , 95 , 102 ]. Concerning fungal diversity from a former Hg mining plant in Rudňany, Slovakia, Cladosporium cladosporioides , Penicillium spp., Aspergillus spp., and Fusarium oxysporum species were recovered [ 88 ].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…188/2003 in the Slovak Republic. Actually, the fungal communities are able to accept even greater concentrations of heavy metals in the soil [36,37], and changes in their communities are smaller than in the bacterial communities [38,39,40]. On the other hand, the opposite effect was observed by Mossa et al [41] and Lin et al [42].…”
Section: Discussionmentioning
confidence: 99%
“…They have demonstrated potential tolerance and remediation abilities towards various HMs, including lead, cadmium, chromium, iron, copper, cobalt, nickel, zinc, and manganese, found in contaminated wastewater. These fungi are characterized as multi-metal-adsorptive fungi [ 5 , [38] , [39] , [40] , [41] ]. Furthermore, Table 3 indicated that Verticillium species showed the highest IC 50 and MIC values against Fe 2+ (1.60–2.25 and 2.19–3.27 g/L) followed by Zn 2+ (1.52–1.73 and 2.10–2.95 g/L), Ag + (1.23–1.70 and 1.99–2.25 g/L), and As 3+ (1.18–1.49 and 1.98–2.20 g/L), respectively while Clavispora species exhibited higher resistant values toward As 3+ followed by Cr 6+ and Cu 2+ (IC 50 = 1.70–2.05, 1.47–2.00 and 1.15–2.16 g/L with MIC values 2.60–3.76, 2.50–3.0 and 2.20–3.62 g/L, respectively).…”
Section: Resultsmentioning
confidence: 99%